Acute urinary retention in benign prostatic hyperplasia: Risk factors and current management - K Muruganandham; Deepak Dubey; Rakesh Kapoor (Indian Journal of Urology, 2007)
Acute urinary retention (AUR) is one of the most significant, uncomfortable and inconvenient event in the natural history of benign prostatic hyperplasia (BPH). The immediate treatment is bladder decompression using urethral or suprapubic catheterization. Several factors have been identified that are associated with or precipitate AUR. It is useful to classify AUR as BPH-related or not, than spontaneous or precipitated when the initial management is considered. Use of prophylactic 5 a-reductase inhibitors can prevent AUR in men with BPH having moderate to severe lower urinary tract symptoms and large prostate size. Alpha blockers can prevent AUR in symptomatic BPH patients and also facilitate catheter removal following episodes of spontaneous AUR. Anticholinergics can be safely combined with alpha blockers in symptomatic BPH patients without increasing the risk of AUR. Surgical treatment carries a higher rate of morbidity and mortality in men presenting with AUR compared to those presenting with symptoms alone. Urgent prostatic surgery after AUR is associated with greater morbidity and mortality than delayed prostatectomy. Alpha blockers mainly help to delay the surgery and may avoid surgery altogether in a subgroup of patients. TURP remains the "gold standard" if a trial without catheter fails. Alternative minimally invasive procedures can be considered in poor-risk patients, but its value is yet to be established.